ANALISIS TINDAK TUTUR ILOKUSI MASYARAKAT JORONG RAGEH NAGARI BUKIK SIKUMPA KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Wirda Linda; Asih Ria Ningsih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The background of the problem in this research is, the mixing of language in the use of language in Jorong Rageh. The purpose of this study is to describe the use of ilokusi speech acts in Jorong Rageh Nagari Bukik Sikimpa District Lareh Sago Halaban District Lima Puluh Kota. This type of research is qualitative with descriptive method. The object of this research is Jorong Rageh Nagari Bukik Sikumpa Society. The Techniques of collection data is using listening techniques. The first step in collecting data is the researcher directly go to the informant’s house that will be observed; second, the researcher observes every speech the informant says; third, the researcher asks questions to informants to say their speech; fourth, the researchers recorded every speech the informant said; fifth, transcribing data in writing as a result of the speech data obtained from the informant. Based on the research conducted found a number of acts of speech ilocusi in Jorong Rageh region Bukik Sikumpa society. From these number can be specified as follows: assertive; directive speech; commissive speech; expressive speech. Thus, the dominant speech uttered by the Jorong Society of the Nagari Desert Hall is an assertive act of speech.